2008
DOI: 10.1080/13651820802392338
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting outcome after Frey procedure for chronic pancreatitis

Abstract: Frey procedure can be performed with zero mortality and low morbidity in a high-volume center. It provides good pain relief in majority of the patients. Volume of the head mass cored affects pain outcome. Correlation between poor results in terms of pain relief and weight loss following Frey's procedure, and small duct disease supports the view that duct diameter is an important predictor of pain relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 32 publications
1
7
1
Order By: Relevance
“…However, there were no major complications in our institution. Another study concluded that patients with pancreatic stenting before operation had higher rates of postoperative pancreatic fistula than patients with nonpancreatic stenting [27]. In our case, previous pancreatic stenting did not increase the risk of pancreatic fistula.…”
Section: Discussionsupporting
confidence: 44%
“…However, there were no major complications in our institution. Another study concluded that patients with pancreatic stenting before operation had higher rates of postoperative pancreatic fistula than patients with nonpancreatic stenting [27]. In our case, previous pancreatic stenting did not increase the risk of pancreatic fistula.…”
Section: Discussionsupporting
confidence: 44%
“…The most frequent [4,5,7,8,10,14,16,18,22]. The median or mean increase of body weight ranged from 0.99 to 7.8 (median ¼ 5.6) kg (n ¼ 264) [4,5,7,11,14,16,18,19,22,28]. Eighty-five (17.3%) of 492 patients and 89 (30.7%) of 290 developed new onset diabetes [4e11, 14,16,18e28] and new onset exocrine insufficiency [4,5,7,8,14,16,18e23,26] respectively.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…In comparison with Beger's procedure, Frey's pancreaticojejunostomy is easier to perform and has low surgical risk. [46]…”
Section: Introductionmentioning
confidence: 99%